GE_GERICHTE P/22723/2017 vom 25. Mai 2021 - GE Cour de justice (2021)
VICE DE FORME;CONTRAINTE SEXUELLE;VIOL;LÉSION CORPORELLE SIMPLE;FIXATION DE LA PEINE;PARTIE CIVILE | CPP.409.al1; CP.189; CP.190; CP.123; CPP.122